FORMING OF HOLLOW SLUGS OF CAST IRON WITH GLOBULAR GRAPHITE IN CONDITIONS OF WALL CRYSTALLIZATIO - V. F. Bevza; E. I. Marukovich; V. P. Grusha (Литьë и металлургия)
The description of conditions of the formation\^ excluding formation of shrinkage cavities and porosity in castings is given, the analysis of dynamics of change of specific heat flow rate andfreezing rate of cast iron during formation time is resulted, influence of preshrinkage expansion of cast iron on geometrical parametres of castings is shown.